The evolutionary status of protostellar clumps hosting class II methanol masers. Issue 2 (14th February 2020) - Jones, B M; Fuller, G A; Breen, S L; Avison, A; Green, J A; Traficante, A; Elia, D; Ellingsen, S P; Voronkov, M A; Merello, M; Molinari, S; Schisano, E
ABSTRACT: The Methanol MultiBeam survey (MMB) provides the most complete sample of Galactic massive young stellar objects (MYSOs) hosting 6.7 GHz class II methanol masers. We characterize the properties of these maser sources using dust emission detected by the Herschel Infrared Galactic Plane Survey (Hi-GAL) to assess their evolutionary state. Associating 731 (73 per cent) of MMB sources with compact emission at four Hi-GAL wavelengths, we derive clump properties and define the requirements of an MYSO to host a 6.7 GHz maser. The median far-infrared (FIR) mass and luminosity are 630 M⊙ and 2500 L⊙ for sources on the near side of Galactic centre and 3200 M⊙ and 10000 L⊙ for more distant sources. The median luminosity-to-mass ratio is similar for both at ∼4.2 L⊙ M⊙ −1 . We identify an apparent minimum 70 μ m luminosity required to sustain a methanol maser of a given luminosity (with L_70 L_6.7 ^0.6 ). The maser host clumps have higher mass and higher FIR luminosities than the general Galactic population of protostellar MYSOs. Using principal component analysis, we find 896 protostellar clumps satisfy the requirements to host a methanol maser but lack a detection in the MMB. Finding a 70 μ m flux density deficiency in these objects, we favour the scenario in which these objects are evolved beyond the age where a luminous 6.7 GHz maser can be sustained. Finally, segregation by association with secondary maser species identifies evolutionary differences within the population of 6.7GHz sources.